Pengaruh Dukungan Manajemen Puncak terhadap Efektifitas Audit Internal dan Dampaknya pada Tata Kelola Perguruan Tinggi yang Baik - Bakri Bakri; Mahfiza Mahfiza (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the effect of top management support on internal audit effectiveness and the effect of internal audit effectiveness on good university governance. The methodology used in this research is quantitative, with an explanatory research approach, to obtain a description systematically, factually, and accurately regarding the facts, characteristics, and relationships between the variables studied. The reason the researcher chose this method was because the researcher wanted to get a fundamental answer about cause and effect by analyzing the factors that caused the phenomenon in the concept raised in the study. The results of the study prove that top management support affects the effectiveness of internal audits. Top management, namely the rector, provides an excellent response to audit findings, so top management is committed to strengthening internal audit by responding to audit findings by the internal control unit. The effectiveness of internal audits affects good university governance. Internal audits at state Islamic religious universities run effectively where, in carrying out their duties, they have a clear scope of duties, good audit planning, are supervised during the audit, and establish effective communication with the auditee. The role of internal audit effectively in an organization in this case higher education will improve good governance, which can increase accountability, for example, the financial statements of the Religious University are submitted to the Ministry of Religion as a form of performance accountability, in addition it will also increase transparency with the Ministry of Religion's availability to provide information to the public, the role of internal audit will also be able to increase participation, where the budget process involves all levels, budget setting and budget changes based on the approval of the ministry of religion, and every procurement of goods is informed to the public in the process.